What Do Science Communicators Talk About When They Talk About Science Communications? Engaging With the Engagers. (April 2015) - Cormick, Craig; Nielssen, Oona; Ashworth, Peta; La Salle, John; Saab, Carol
A series of workshops on impediments and solutions to best practice in science communication in Australia not only provided insights into the diversity of the community of practice but also reflected discords between best practice and popular ideas among practitioners.